Immunometabolism is a key factor for the persistent spontaneous elite control of HIV-1 infectionResearch in context - Laura Tarancon-Diez; Esther Rodríguez-Gallego; Anna Rull; Joaquim Peraire; Consuelo Viladés; Irene Portilla; María Reyes Jimenez-Leon; Verónica Alba; Pol Herrero; Manuel Leal; Ezequiel Ruiz-Mateos; Francesc Vidal (EBioMedicine, 2019)
Background: Approximately 25% of elite controllers (ECs) lose their virological control by mechanisms that are only partially known. Recently, immunovirological and proteomic factors have been associated to the loss of spontaneous control. Our aim was to perform a metabolomic approach to identify the underlying mechanistic pathways and potential biomarkers associated with this loss of control. Methods: Plasma samples from EC who spontaneously lost virological control (Transient Controllers, TC, n = 8), at two and one year before the loss of control, were compared with a control group of EC who persistently maintained virological control during the same follow-up period (Persistent Controllers, PC, n = 8). The determination of metabolites and plasma lipids was performed by GC-qTOF and LC-qTOF using targeted and untargeted approaches. Metabolite levels were associated with the polyfunctionality of HIV-specific CD8+T-cell response. Findings: Our data suggest that, before the loss of control, TCs showed a specific circulating metabolomic profile characterized by aerobic glycolytic metabolism, deregulated mitochondrial function, oxidative stress and increased immunological activation. In addition, CD8+ T-cell polyfunctionality was strongly associated with metabolite levels. Finally, valine was the main differentiating factor between TCs and PCs. Interpretation: All these metabolomic differences should be considered not only as potential biomarkers but also as therapeutic targets in HIV infection. Fund: This work was supported by grants from Fondo de Investigación Sanitaria, Instituto de Salud Carlos III, Fondos FEDER; Red de Investigación en Sida, Gilead Fellowship program, Spanish Ministry of Education and Spanish Ministry of Economy and Competitiveness. Keywords: Elite controllers, Energy metabolism, HIV-1, Immunometabolism, Loss of control, Metabolomic profile